An introduction to cognitive psychology : processes and disorders - Groome, David, 1946- (Routledge, 2021)
"An Introduction to Cognitive Psychology: Processes and Disorders provides a comprehensive, yet accessible, overview of the field for undergraduate students. The fourth edition has been thoroughly revised throughout to provide a comprehensive introduction to the core topics of cognition, including memory, perception, thinking, and language. Uniquely, alongside coverage of normal cognitive function, the book also includes chapters on clinical disorders such as agnosia, amnesia, and aphasia, providing a more balanced insight into the nature of cognition and its related disorders. Key features: Completely revised and updated throughout to provide a comprehensive overview of current thinking in the field Accessibly written by experienced textbook authors and academic experts, including Mike Eysenck and Sophie Scott A new chapter on Problem Solving, written by Fernand Gobet, a leading authority in the field Greater coverage of neuropsychological disorders, with additional coverage of brain imaging research Features a wealth of real-world examples throughout to bring research to life Specially designed textbook features, chapter summaries, further reading, and a glossary of key terms An Introduction to Cognitive Psychology will appeal to all students on an undergraduate psychology degree course, as well as to those studying in related clinical professions"--